Aerodynamic and thermal interference between two building models. Issue 1 (March 2020) - Korobkov, S; Gnyrya, A; Terekhov, V
Abstract: the paper considers aerodynamic and thermal interference of separated flows between two square prisms arranged at a short distance from each other. It is shown how relative positions of the square prisms affect the specific phenomena caused by the airflow interactions. This work is the experimental study of aerodynamic and thermal interference effects on two square prisms or building models depending on their relative positions. A strong difference is shown between aerodynamic and thermal interferences observed in the airflow behind two tandem models. The thermal interference effect turns to be rather conservative as compared to the aerodynamic. Using the interference parameters one can easily analyze the extreme values of the pressure and thermal flows interfering with the building models depending on many factors, including relative model positions.